PKM Karya Tulis Ilmiah - Hajrah Hamzah; Sahade Sahade (DEDIKASI, 2020)
The Community Partnership Program (PKM) partners are teachers of SD Pangkep. The problems are: (1) lack of knowledge about scientific writing (2) lack of skills in writing scientific papers and, (3) teachers at SD Pangkep in carrying out their functions are required to be professionally. The external target is the process of compiling Scientific Writing. The methods used are: lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners have knowledge in the field of Scientific Writing, (2) partners have the skills to compile Scientific Writing and, (3) partners have the ability to increase knowledge of the ability to write Scientific Papers.